2020
DOI: 10.3390/brainsci10110773
|View full text |Cite
|
Sign up to set email alerts
|

Exergames and Telerehabilitation on Smartphones to Improve Balance in Stroke Patients

Abstract: Stroke is currently the world’s second cause of disability. It can cause deficits such as postural control, and telerehabilitation could improve the therapeutic dose as well as functional results. The aim of this work is to determine the effectiveness and usability of a low-cost telerehabilitation system in patients with stroke. We developed a telerehabilitation system based on exergames on smartphones, inertial sensors, and a cloud database. We trained the balance of six participants (three men and three wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…This resulted in the inclusion of 306 studies for full-text screening. Among these, 34 trials 9,10,33-64 were retained for the qualitative synthesis and 30 were selected for the meta-analysis. A flow chart diagram illustrating the selection process is presented in Figure 1.
Figure 1.Selection process represented through a flow chart diagram.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This resulted in the inclusion of 306 studies for full-text screening. Among these, 34 trials 9,10,33-64 were retained for the qualitative synthesis and 30 were selected for the meta-analysis. A flow chart diagram illustrating the selection process is presented in Figure 1.
Figure 1.Selection process represented through a flow chart diagram.
…”
Section: Resultsmentioning
confidence: 99%
“…In this review, only four studies evaluated the cost of intervention. 9,33,59,63 Among these, one study performed a cost-effectiveness analysis and showed that its program was more cost-effective than conventional face-to-face therapy. 9 This finding is supported by previous work that conducted cost-effectiveness analysis to compare telerehabilitation programs to conventional therapy in other pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of fall or injury during exercise has to be reduced to a minimum and redressing support in case of balance loss or standing up after a fall has to be assured [36]. Probably due to safety procedures, some studies found balance to be one of the outcomes where TR did not prove its efficacy [11]; however, there are some research results that suggest the opposite [33,37]. Therefore, when the exercises performed at home target walking and balance, it is of importance to ensure the safety of therapy sessions with the presence of a family member or another informal caregiver who can supervise, support and help the patient in case of loss of balance (Figure 1).…”
Section: How To Organize Tr At Patient's Home?mentioning
confidence: 99%
“…Many rehabilitation studies do not focus on participation outcomes but rather continue to measure and intervene at the level of body functions [ 13 , 18 , 19 ]. The same problem recurs in the telerehabilitation field; thus, most studies that examined the efficacy of telerehabilitation programs for this population focus on body functions such as balance, upper-extremity function, and cognitive skills [ 20 , 21 , 22 , 23 , 24 , 25 ]. Therefore, there is a need for developing telerehabilitation intervention models to facilitate participation and community reintegration for this population that extend beyond impairment remediation approaches (see Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%